Molecular Characterization, Expression Patterns and Binding Properties of Two Pheromone-Binding Proteins from the Oriental Fruit Moth, Grapholita molesta (Busck) - Yue-qin SONG; Jun-feng DONG; Hui-li QIAO; Jun-xiang WU (Journal of Integrative Agriculture, 2014)
Insect pheromone-binding proteins (PBPs) play important roles in transporting hydrophobic pheromone components across the sensillum lymph to the surface of olfactory receptors (ORs). However, the PBPs of the oriental fruit moth, Grapholita molesta, an important destructive pest of stone fruits worldwide, are not well characterized. In this study, two new putative PBP genes, GmolPBP2 and GmolPBP3, were identified from G. molesta antennae. The deduced amino-acid sequences of these two putative PBP genes are characteristic of the odorant binding protein family, containing six conserved cysteine residues. The genomic DNA sequence of each gene contained two introns. However, the lengths and positions of the introns differed. RT-PCR analyses revealed that the two GmolPBP genes are only expressed in the antennae of female and male moths. Quantitative real-time PCR indicated that the transcription levels of GmolPBP2 are far greater than those of GmolPBP3 in both female and male antennae. GmolPBP3 showed higher transcription levels in female antennae than in male antennae, while GmolPBP2 showed similar transcription levels in both female and male antennae. The transcript levels of both genes were significantly different in premating and post-coitum individuals, implying that mating affects the process of sex pheromone reception. To better understand the functions, two GmolPBPs were expressed in Escherichia coli, and the ligand binding assays were conducted. Results showed that GmolPBP2 has strong binding affinities to two sex pheromone components, E8–12:Ac and Z8–12:Ac, as well as weaker binding affinities to Z8-12:OH and 12:OH. GmolPBP2 also bound some ordinary odor molecules. However, the affinity of GmolPBP3 to both sex pheromones and ordinary odor molecules was very weak. These results show that GmolPBP2 plays the main role in pheromone discrimination and recognition in the oriental fruit moth.